The entangled fates of plastics and climate change - Neil Tangri (Cambridge Prisms: Plastics)
Plastics and climate change are inseparable issues, both materially and geopolitically. Plastics are derived almost entirely from fossil fuels and have an enormous greenhouse gas footprint. Aligning with the Paris Agreement requires rapid, dramatic decreases in plastic production, contravening the industry’s plans to continue expanding production. The oil, gas and petrochemical industry wields substantial power in both the climate and plastics treaty negotiations and has used that power to stymie progress in both. Rather than repeat the failures of the climate negotiations, plastics negotiators should seek to create a “plastics club” for ambitious action.